Multidisciplinary aspects of time and time perception COST TD0904 International Workshop, Athens, Greece, October 7-8, 2010, Revised Selected Papers - Vatakis, Argiro (Lecture Notes in Computer Science, 2011)
This book constitutes the documentation of the scientific outcome of the first meeting of the TIMELY network, the International Workshop on Multidisciplinary Aspects of Time and Time Perception, which took place in Athens, Greece, in October 2010. The 21 papers presented were carefully reviewed and selected for inclusion in the book. They cover the following topics: conceptual analysis and measurement of time; exploring factors associated with time perception variability; extending time research to ecologically-valid stimuli and real-world applications; and uncovering the neural correlates of time perception.